2014
DOI: 10.1590/s0102-05362014000200018
|View full text |Cite
|
Sign up to set email alerts
|

Yield of tomato fruits in relation to silicon sources and rates

Abstract: There is controversy about the benefits of silicon (Si) on tomato plants. This element has structural and metabolic functions in the physiology of plants, generating benefits that may result in increased productivity of various plant species. Thus, the aim of this study was to evaluate the phytotechnical characteristics and the productivity of tomato plants according to the rates and sources of Si. The design was established in randomized blocks with factorial 3x5, corresponding to three sources of silicate (c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
29
0
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(42 citation statements)
references
References 13 publications
5
29
0
4
Order By: Relevance
“…This may be the factor responsible for firmness increasing in the fruit. The Si fertilization in tomato plants reduces the occurrence of cracked fruits, which are classified as noncommercial (Marodin et al, 2014). Fruit firmness is an essential characteristic of post harvest conservation during transportation and commercialization, and it is related to shelf life.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This may be the factor responsible for firmness increasing in the fruit. The Si fertilization in tomato plants reduces the occurrence of cracked fruits, which are classified as noncommercial (Marodin et al, 2014). Fruit firmness is an essential characteristic of post harvest conservation during transportation and commercialization, and it is related to shelf life.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, silicon fertilization promotes an increase in fruit yield in the tomato crop (Marodin et al, 2014). Despite the proven effects of Si on the mentioned metabolic processes, little information on its effects on traits related to post-harvest quality can be found.…”
Section: Palavras-chavementioning
confidence: 99%
“…Applied Si was readily taken up and accrued in plant tissues (like root, shoot, leaves and grains), increased P nutrition and nitrogen use efficiency with increase in Si supply (Neu et al, 2017). Marodin et al, (2014) suggested that the application of Si using potassium or calcium silicates increased the levels of Si in tomato leaves with increase in crop yield at the highest Si rate (800 kg ha -1 ). Calcium silicate application to saline soil at 100 or 75 mg kg -1 might be a useful strategy for reducing the impact of salinity on rice while improving plant growth, yield, P, Si and K nutrition by reducing the accumulation or uptake of Na in plant parts.…”
Section: Discussionmentioning
confidence: 99%
“…The Si treatment increased the yield and reduced the cracked/damaged tomato fruits (Marodin et al, 2014). Five applications of potassium silicate over 12 days significantly reduced the severity of the tomatoes' powdery mildew (Yanar, Yanar, & Gebologlu, 2011) and increased the plants' resistance to disease, which is associated with active and/or passive mechanisms (Ouellette et al, 2017).…”
Section: Introductionmentioning
confidence: 99%